(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article examines the main scientific research methods used in modern pedagogical inquiry, including observation, interview, questionnaire, document analysis, tests, pedagogical analysis, children’s creative work analysis, pedagogical experiment, and mathematical-statistical methods. The theoretical foundations and practical significance of these methods are analyzed based on pages 15–20 of the textbook Umumiy Pedagogika. The study argues that these methods play a crucial role in improving the quality of education, understanding learners’ development, and organizing pedagogical processes on a scientific basis.